Narrative as a Radial Category - Badio, Janusz (Studia Anglica Posnaniensia, 2020)
Narrative is a complex and elusive category of cognition, culture, communication and language. An attempt has been made in this article with a large enough theoretical scope to consider the possibility of treating narrative as a radial category. To this end, the definition and characterisation of radiality is provided together with explanation of what it might mean to apply this term to the complex language-discourse unit of narrative. The prototype of this category involves features, functions, and ICMs. It has multiple representations with only family resemblance, involves more obvious exemplars and variable abstract knowledge structures. In particular, section one looks at the radiality question and what it might mean to think of the meaning of narrative in general. Section two focuses on centrality. Sections three to five deal with schematic representations of narrative and provide examples of extending the most subsuming schema of the Action Chain Model from cognitive linguistics and Labov’s Narrative Schema to various other types of conversational narrative, children’s dramatic plays, tactical narratives, story rounds, jokes, poems, current news articles on the Internet, images, and advertisements.